Investigation of Energy Consumption Optimization Methods in Wireless Sensor Networks - Seyede zohre majidiana (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the most important issues in wireless sensor networks is the issue of severe energy constraints. Also, since the performance of sensor networks is highly dependent on the life of the network, it is vital to consider energy storage algorithms in the design of long-life sensor networks. This paper discusses the Nature-Sync-inspired Algorithm (ACOTS) algorithm based on Ant Colony optimization to provide an energy efficient solution for simultaneous synchronization solution in WSN And it was observed that it drastically reduces the number of packets sent and received during the synchronization process. This helps solve synchronization time and also creates an energy efficient network with less energy consumption. The proposed ACOTS algorithm is compared with existing algorithms. It is broadcast reference synchronization (RBS) and time synchronization protocol for sensor network (TPSN). Comparative results show that ACOTS uses less message exchange than other schemes.